A sign of The Times: an APPRAISAL analysis of the imagined community’s bonding in letters to a South African newspaper - Smith, Jade; Adendorff, Ralph (Stellenbosch Papers in Linguistics Plus, 2022)
This article investigates how writers to The Times, formerly a daily national newspaper, used APPRAISAL strategies in letters to the editor to form the bonds that unified an imagined community of readership. The couplings of interpersonal and ideational meaning around which the community affiliated are revealed by an APPRAISAL analysis. Conclusions drawn from this information indicate the nature of the imagined community in terms of how the members viewed their agency, and the cohesion of the group. Main findings show that the community affiliated around evaluations of South Africa’s ruling party, the African National Congress (ANC), and its leader at the time, Jacob Zuma, but did so very differently. The Times’ writers also tended to be individualistic and did not rely on other community members to solve the problems they identified.